Análise das manifestações patológicas do prédio da Biblioteca do Setor Sul da UFAM pelo método GUT - Fernandes, Iana Vieira (Brasil, 2023)
Even with the technological advancement of construction processes in recent decades, the emergence of pathological manifestations is still inevitable, whether due to design, execution or use errors. These compromise the performance, functionality and stability of the structure, and entail costs that could be avoided. This work aims to analyze, based on research and consulted references, the pathological manifestations of the building of the South Sector Library, at the Federal University of Amazonas, through the GUT Method, and propose an order of priority for solving the problem. Despite being a recent construction, it already has a high incidence of pathologies of different types and origins. From the results of the possible causes of these manifestations, intervention measures are proposed, ranging from paint repairs to reinforcement of structural parts. The importance of this study is emphasized for the prevention and care to be taken in new University works.